PENGELOLAAN NYERI PUNGGUNG DENGAN SENAM HAMIL - Alaida, Ari Isma; Rahmayani, Erna; Setyarini, Arika Indah (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Back pain in pregnant women occurs due to impaired blood circulation due to enlargement and pressure of the uterus, especially in the pelvic veins when sitting and the inferior vena cava when lying down and capillary absorption. The aim is to identify scientific evidence related to the management of back pain with pregnancy exercise. The data sources used in this research are scientific journals. Data collection was carried out using thedatabases Google Scholar, Pubmed and Semantic Scholar. In conducting a search for national journals, researchers used keywords, namely, while in international journals they used the keywords back pain, pregnant women, pregnant exerciseback pain, pregnant women, pregnant exercise. Data analysis was carried out by reviewing scientific journals found on the management of back pain with pregnancy exercise. Study found that pregnancy exercise had an effect in reducing the intensity of back pain for pregnant women with the time of giving pregnant exercise during the 2 and 3 trimesters of pregnancy with an interval of at least 1 time a week. From all journals shows that pregnancy exercise has an effect on reducing the intensity of back pain in pregnant women. Based on the results of this study, it is expected that pregnancy exercise can be an alternative solution in providing midwifery care to pregnant women who experience back pain and pregnant women can carry out exercise independently.